Dermoscopy of inverted follicular keratosis: study of 12 cases. (28th March 2016) - Llambrich, A.; Zaballos, P.; Taberner, R; Terrasa, F.; Bañuls, J.; Pizarro, A.; Malvehy, J.; Puig, S.
Summary: Background: Inverted follicular keratosis (IFK) is an uncommon benign tumour of the follicular infundibulum, which is often misdiagnosed clinically as other keratinizing tumours, and commonly diagnosed correctly by histopathology. There are few reports about the dermoscopic findings of this lesion. Aim: To evaluate the dermoscopic features of IFK. Methods: The dermoscopic structures and patterns in digital dermoscopic images of 12 histopathologically confirmed cases of IFK collected from 5 hospitals in Spain were evaluated. Results: A keratoacanthoma (KA)‐like pattern composed of central keratin surrounded by hairpin vessels in a radial arrangement was the most common pattern in IFK (58.3%). The second most common pattern was composed of a yellowish‐white amorphous central area surrounded by vascular structures in a radial arrangement (33.3%). The remaining case showed a pattern composed of a yellowish‐white amorphous central area with milky red globules. Vascular structures were present in all cases, with a monomorphic pattern in seven cases and a polymorphic pattern in five, mainly with radial arrangement. Arborizing vessels, linear irregular vessels, corkscrew vessels and milky red globules were present in some cases. Conclusions: We describe the two main patterns of IFK. Lesions with a KA‐like pattern are clinically and dermoscopically undistinguishable from KA and squamous cell carcinoma. Cases with a polymorphic vascular pattern could be confused with malignant tumours, including basal cell carcinoma and amelanotic melanoma.